2022
DOI: 10.1021/acsaem.2c00537
|View full text |Cite
|
Sign up to set email alerts
|

Application of Porous Coordination Polymer Containing Aromatic Azo Linkers as Cathode-Active Materials in Sodium-Ion Batteries

Abstract: Aromatic azo compounds have been reported as organic active materials of sodium-ion and lithium-ion batteries owing to the redox reaction of azo groups (NN) and the introduction of insoluble groups. In this study, we investigated a method to realize both high capacity and good cycle performance of sodium-ion batteries by combining aromatic azo compounds with redox-active atoms insoluble in the electrolyte. Moreover, the metal–organic framework (MOF) CPL-4 ([Cu2(pzdc)2(azpy)], pzdc = pyrazine-2,3-dicarboxylate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 43 publications
(67 reference statements)
0
15
0
Order By: Relevance
“…These findings pave the way to the development of new cathode active materials for sodium-ion batteries. [51] As described above, azo polymers and frameworks show high battery performance because of their insolubility in organic solvents and the tunable HOMO and LUMO energies of π-conjugated structures. These findings facilitate the design of azo compounds as the active materials of rechargeable batteries with both high capacity and high rate capability and suggest that these goals can be achieved using the soft crystal features of COFs and MOFs (Table 4).…”
Section: Methodsmentioning
confidence: 98%
“…These findings pave the way to the development of new cathode active materials for sodium-ion batteries. [51] As described above, azo polymers and frameworks show high battery performance because of their insolubility in organic solvents and the tunable HOMO and LUMO energies of π-conjugated structures. These findings facilitate the design of azo compounds as the active materials of rechargeable batteries with both high capacity and high rate capability and suggest that these goals can be achieved using the soft crystal features of COFs and MOFs (Table 4).…”
Section: Methodsmentioning
confidence: 98%
“…In addition, 4,4′‐azopyridine showed a higher voltage (2.2 V vs. Na + /Na, 2.5 V vs. Li + /Li) than azobenzene with metal carboxylate moieties (1.2 V vs. Na + /Na, 1.5 V vs. Li + /Li), [50] which indicated that CPL‐4 is a promising azo‐based cathode active material. These findings pave the way to the development of new cathode active materials for sodium‐ion batteries [51] …”
Section: Rechargeable Batteriesmentioning
confidence: 85%
“…In particular, MOFs with redoxactive organic ligands have attracted significant attention as potential electroactive materials for rechargeable batteries. 16−26 So far, we have applied such redox-active MOFs to cathodes of LIBs and SIBs, where anthraquinone dicarboxylate, 27,28 disulfide organic linkages, 29 and aromatic azo compounds 30 have been used as redox-active ligands. In these studies, we identified dual-ion exchange, electrochemically dynamic disulfide covalent bonds, and sodium-ion-selective insertions as novel phenomena.…”
Section: ■ Introductionmentioning
confidence: 99%